Regulation of miRNA strand selection: follow the leader?. (11th August 2014) - Meijer, Hedda A.; Smith, Ewan M.; Bushell, Martin
Abstract : miRNA strand selection is the process that determines which of the two strands in a miRNA duplex becomes the active strand that is incorporated into the RISC (RNA-induced silencing complex) (named the guide strand, leading strand or miR) and which one gets degraded (the passenger strand or miR*). Thermodynamic features of the duplex appear to play an important role in this decision; the strand with the weakest binding at its 5′-end is more likely to become the guide strand. Other key characteristics of human miRNA guide strands are a U-bias at the 5′-end and an excess of purines, whereas the passenger strands have a C-bias at the 5′-end and an excess of pyrimidines. Several proteins are known to play a role in strand selection [Ago (Argonaute), DICER, TRBP (trans-activation response RNA-binding protein), PACT (protein activator of dsRNA-dependent protein kinase) and Xrn-1/2]; however, the mechanisms by which these proteins act are largely unknown. For several miRNAs the miR/miR* ratio varies dependent on cell type, developmental stage and in different disease states, suggesting that strand selection is a tightly controlled process. The present review discusses our current knowledge regarding the factors and processes involved in strand selection and the many questions that still remain.